2000
DOI: 10.1071/ea99106
|View full text |Cite
|
Sign up to set email alerts
|

Surface soil moisture and stubble management practice effects on the progress of infection of wheat by Fusarium pseudograminearum

Abstract: The influence of surface soil moisture and stubble management practices on the progress of infection of wheat by Fusarium pseudograminearum, the cause of crown rot, was assessed in a field trial at Moree in northern New South Wales during the growing seasons of 1994, 1995 and 1996 by analysis of infection progress curves. During the dry season of 1994, wheat was sown into dry surface soil. Increases in incidence of infection followed rainfall events that raised the water content of the surface soil above the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…The adoption of conservation tillage increases inoculum pressures, cropping intensity, crown depths, and early season moisture. All of these factors have been shown to increase crown rot severity and together with species differences may explain much of the recent increases in FCR severity (Cook 1980, Swan et al 2000Wildermuth et al 2001). …”
Section: Discussionmentioning
confidence: 99%
“…The adoption of conservation tillage increases inoculum pressures, cropping intensity, crown depths, and early season moisture. All of these factors have been shown to increase crown rot severity and together with species differences may explain much of the recent increases in FCR severity (Cook 1980, Swan et al 2000Wildermuth et al 2001). …”
Section: Discussionmentioning
confidence: 99%
“…are available. Under different depth and type of implement used conservation tillage decreased (Damm, 1998a, b;Weber et al, 2001), increased (Bailey and Duczek, 1996) or had no effect (ArnoldReimer, 1994;Swan et al, 2000;Wildermuth et al, 1997) on Fusarium foot and root rot. Most studies on Fusarium head blight or ear rot documented a significant increase (Beck and Lepschy, 2000;Dill-Macky and Jones, 2000;Yi et al, 2001) or no increase of infections in case of conservation tillage treatments (Bahle and Leist, 1997;Flett and McLaren, 1998;Miller et al, 1998;Steinkellner et al, 2002).…”
Section: Introductionmentioning
confidence: 97%
“…The first of these was a long-term stubble management trial running from 1986-1996. Disease incidence and yield data from this trial for 1986-1991 have been presented as site B in Burgess et al (1993), and for 1994-1996 in Swan et al (2000). Disease incidence, but not yield, for 1992 and 1993 were reported by Burgess et al (1996) as the continuous wheat treatment in a sorghum rotation experiment.…”
Section: Data Sourcesmentioning
confidence: 97%
“…These included incidence of the disease in the previous crop, and yield of the previous crop because it had been noted that disease incidence was low in years following low-yielding crops (Burgess et al 2001). Swan et al (2000) reported that rate of disease progress within seasons was dependent on soil moisture, with increases in incidence following major rainfall events. Therefore in-crop rainfall and the number of in-crop rainfall events greater than 10 mm were used.…”
Section: Regression Analysismentioning
confidence: 98%